Job changes and hours changes: Understanding the path of labour supply adjustment - Richard W. Blundell; Mike Brewer; Marco Francesconi (Institute for the Study of Labor (IZA), 2007)
This paper uses British panel data to investigate single women's labour supply changes in response to three tax and benefit policy reforms that occurred in the 1990s. These reforms changed individuals' work incentives and we use them to identify changes in labour supply. We find evidence of small hours of work effects for two of such reforms. A third reform in 1999 instead led to a significant increase in single mothers' hours of work. The mechanism by which the labour supply adjustments were made occurred largely through job changes rather than hours changes with the same employer. These results are confirmed when we look at hours changes by stated labour supply preferences. Finally, we find little overall effect of the reforms on wages.
Keywords: 330; job mobility; hours flexibility; labour supply preferences; hours-wage trade-off; monopsony; Arbeitszeit; Arbeitszeitflexibilisierung; Arbeitsmobilität; Teilzeitarbeit; Weibliche Arbeitskräfte; Großbritannien